2016
DOI: 10.3343/alm.2016.36.6.590
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Suppression of Tumorigenicity 2 and Echocardiography in Sepsis

Abstract: Soluble suppression of tumorigenicity 2 (sST2) has emerged as a biomarker of cardiac stretch or remodeling, and has demonstrated a role in acutely decompensated heart failure. However, its role in sepsis-induced cardiac dysfunction is still unknown. We explored whether sST2 serum concentration reflects either systolic or diastolic dysfunction as measured by Doppler echocardiography. In a total of 127 patients with sepsis, correlations between sST2 and blood pressure, left ventricular (LV) ejection fraction, LV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Multiple organ failure is a complex syndrome involving diverse pathways and pathological processes in sepsis [2425]. Cardiac failure is a major risk factor of in-hospital mortality [26]. In addition, cardiac and renal diseases interact in a complex bidirectional and interdependent manner in both acute and chronic settings; sepsis is a representative disease entity of the organ crosstalk between the heart and kidney [24].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple organ failure is a complex syndrome involving diverse pathways and pathological processes in sepsis [2425]. Cardiac failure is a major risk factor of in-hospital mortality [26]. In addition, cardiac and renal diseases interact in a complex bidirectional and interdependent manner in both acute and chronic settings; sepsis is a representative disease entity of the organ crosstalk between the heart and kidney [24].…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis study performed by Aimo et al (2017) mentioned that plasma sST2 has prognostic value with respect to all-cause and cardiovascular death [31], and associated with cardiac concentric hypertrophy in patients with metabolic syndrome [32]. Circulating sST2 levels also correlate with a worse phenotype of disease including adverse remodeling and fibrosis, cardiac dysfunction, impaired hemodynamics and higher risk of progression [33,34]. Therefore, it was supposed that plasma level of sST2 would increase in the early stage of LHV.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in a meta-analysis plasma sST2 has been demonstrated to have a prognostic value with respect to all-cause and cardiovascular death as well as the composite outcome of all-cause death or HF hospitalization [33]. Previous studies already also have shown that plasma sST2 was not only useful biomarker for predicting development of stress cardiomyopathy [34] but also has prognostic role in patients with sepsis [35,36] and correlated with left ventricular structure and function in patients with metabolic syndrome [37]. Renin is the well-known enzyme of the Renin Angiotensin Aldosteron System, which plays central role in the regulation of blood pressure and the development of LVH [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, findings on sST2 in sepsis have been ambiguous. The study of Yang et al reported that sST2 levels were not associated with cardiac function in septic patients ( 18 ). Studies determining the relationship between sST2 and SIC to predict prognosis in affected patients should be conducted.…”
Section: Introductionmentioning
confidence: 99%